Signifyin' Cinema: Rudy Ray Moore and the Quality of Badness. - Munby, Jonathan (Journal for Cultural Research, 2007)
This article engages the limits of both film and race studies in their approach to heterogeneous and "low" forms of African American cultural production through an analysis of the films of Rudy Ray Moore. While Moore's films have been almost entirely overlooked in both film studies and black studies, they were extremely popular among black youth of the 1970s and have exerted a powerful influence on today's hardcore hip hop artists (and their understanding of how to turn black market entrepreneurship into global enterprise). The theory of "signifying", advanced most rigorously by black literary theorist Henry Louis Gates Jr, helps explain how and why Moore has slipped through various critical nets - and grounds a claim for why we should take "bad" black film seriously. Close film and context analysis illustrates how Moore's low-budget films "signify" on Hollywood and the system of expectancies that go with putatively "good" filmmaking and reveals the extent to which they constitute a hybrid cultural and multimedia practice. As vehicles designed to elaborate on the badman of black folklore, Moore's films contribute to the long history and rich language of "toasting" in African American oral culture and music. As such, far from being emblematic of black filmmaking's impoverished relationship to mainstream cinema (as a cinema manqué), these films constitute vital precursors to the hip hop music video.